2015
DOI: 10.1038/bjc.2015.281
|View full text |Cite
|
Sign up to set email alerts
|

Target gene mutational pattern in Lynch syndrome colorectal carcinomas according to tumour location and germline mutation

Abstract: Background:We previously reported that the target genes in sporadic mismatch repair (MMR)-deficient colorectal carcinomas (CRCs) in the distal colon differ from those occurring elsewhere in the colon. This study aimed to compare the target gene mutational pattern in microsatellite instability (MSI) CRC from Lynch syndrome patients stratified by tumour location and germline mutation, as well as with that of sporadic disease.Methods:A series of CRC from Lynch syndrome patients was analysed for MSI in genes predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…S1), indicating a potential role of this mutation in colorectal cancer. In addition, it was recently reported that 35% of Lynch syndrome colorectal cancers had the same mutation seen in this study (29). Similarly, the frameshift InDel seen here in 72% of MSI tumors in SETD1B (H8fs) has been reported as a confirmed somatic mutation in colorectal cancer, albeit at a mutation rate of $6% (7).…”
Section: Discussionsupporting
confidence: 82%
“…S1), indicating a potential role of this mutation in colorectal cancer. In addition, it was recently reported that 35% of Lynch syndrome colorectal cancers had the same mutation seen in this study (29). Similarly, the frameshift InDel seen here in 72% of MSI tumors in SETD1B (H8fs) has been reported as a confirmed somatic mutation in colorectal cancer, albeit at a mutation rate of $6% (7).…”
Section: Discussionsupporting
confidence: 82%
“…DNA MMR deficiency is known to underlie MSI and hypermutability in LS and sporadic tumors, but the mutational landscapes may differ depending on the mechanism of MMR gene inactivation [ 7 , 15 ]. Even in LS mutation carriers, MSI is not invariably present but shows tumor type-specific variation, likely reflecting different patterns of clonal growth [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Mutations were common in the genes that coding TGF-b signaling proteins. 15 Specially, those mutations major effected TGFBRII and SMAD4. 16,17 TGFBRII mutations were detected nearly 74% of CRC patients with microsatellite instability (MSI) and did not associated with the patients outcome.…”
Section: Discussionmentioning
confidence: 99%